Cooperative principle in Facebook interaction among collegian - Lusi Elisa; Rina Wahyuni (UAD TEFL International Conference)
One of the main principles guiding people’s communication is the cooperative principle by American linguist Grice. The use of cooperative principle helps people to increase their flexibility and accuracy. The analysis of cooperative principle in a text or conversation shall be the learning for people to communicate well using language with each other. The paper aimed to find out whether the participants under study followed or violated the maxims proposed by Grice. Besides, it was to identify whether the cooperative principles become the participants’ orientation or mere redundant rules. The research employed a descriptive qualitative research of which the data were obtained from the conversation among six workmates in a Flary group discussion on Facebook page. The research founds that the conversation followed and violated the maxims by Grice. Maxim of quantity was the most frequently used by the participants (12.77%). Interestingly, it was also the most frequently violated (63.8%). Despite the violation occurred in the interactions, the conversation was smooth. When the speakers realized about the cooperative principles they had to obey, the conversation became more relaxed, effective, and efficient.